2016
DOI: 10.3389/fnagi.2016.00286
|View full text |Cite
|
Sign up to set email alerts
|

Voice Pitch Elicited Frequency Following Response in Chinese Elderlies

Abstract: Background: Perceptual and electrophysiological studies have found reduced speech discrimination in quiet and noisy environment, delayed neural timing, decreased neural synchrony, and decreased temporal processing ability in elderlies, even those with normal hearing. However, recent studies have also demonstrated that language experience and auditory training enhance the temporal dynamics of sound encoding in the auditory brainstem response (ABR). The purpose of this study was to explore the pitch processing a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 45 publications
1
9
0
Order By: Relevance
“…Our data revealed that although the responses were weaker than the younger adults, older adults’ FFR did not appear to be more susceptible to differing ISI lengths, some as short as 40 ms. The 40 ms ISI has been widely used in the FFR literature for Mandarin Chinese speech stimuli in younger adults (Krishnan et al, 2004 , 2005 ; Jeng et al, 2011 ; Wang et al, 2016 ). In the current study, it did not seem to be too short for the older adults’ FFR, reflected by the two indices, stimulus-to-response correlation coefficient and the pitch strength.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our data revealed that although the responses were weaker than the younger adults, older adults’ FFR did not appear to be more susceptible to differing ISI lengths, some as short as 40 ms. The 40 ms ISI has been widely used in the FFR literature for Mandarin Chinese speech stimuli in younger adults (Krishnan et al, 2004 , 2005 ; Jeng et al, 2011 ; Wang et al, 2016 ). In the current study, it did not seem to be too short for the older adults’ FFR, reflected by the two indices, stimulus-to-response correlation coefficient and the pitch strength.…”
Section: Discussionmentioning
confidence: 99%
“…Pitch strength is defined as the distance between of the maximum of and the minimum of the autocorrelation function. For detailed discussion on these two indices, please refer to our previous work in Jeng and Warrington ( 2011 ) and Wang et al ( 2016 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another form of auditory expertise-musicianship-also produces stronger pitch-tracking responses (Wong et al, 2007). On the other hand, even within tone-language speakers, a decline in FFR pitch tracking is seen in older adults (Wang et al, 2016). Russo et al (Russo et al, 2008) noted weaker pitch tracking in school-age children on the autism spectrum compared to typically developing peers, evocative of the characteristic flat affect in the speech of some autistic individuals and the diminished ability to perceive emotional valence (Matsumoto et al, 2016).…”
Section: Vowels With Changing Pitchmentioning
confidence: 99%
“…For example, the FFR is thought to be related to auditory experience, such that stronger FFRs are observed with greater degrees of musical skill (Musacchia et al, 2007; N. Kraus & Strait, 2015; Parbery-Clark et al, 2012; Wong et al, 2007) or language experience (Krishnan et al, 2005; S Wang et al, 2016Song et al, 2008).…”
Section: Introductionmentioning
confidence: 99%